2022
DOI: 10.1515/medgen-2022-2138
|View full text |Cite
|
Sign up to set email alerts
|

Reduced penetrance of Parkinson’s disease models

Abstract: The etiology and progression of Parkinson’s Disease (PD), the second most prevalent neurological disorder, have been widely investigated for several decades; however, a cure is still lacking. Despite the development of several neurotoxins and animal models to study this rather heterogeneous disease, a complete recapitulation of the neurophysiology and neuropathology of PD has not been fully achieved. One underlying cause for this could be that mutations in PD-associated genes have reduced penetrance. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…However, family studies have revealed monogenic forms of PD in which variation at a single gene locus can be attributed to disease causality [8]. For example, PD-causing autosomal dominant mutations have been identified in the LRRK2, SNCA, and VPS35 genes, and autosomal recessive mutations have been identified in the PARK7 (Dj-1), PRKN (Parkin), and PINK1 genes [7][8][9][10][11]. While the development of single gene disorders is primarily determined by genetics, known and unknown factors can modify disease penetrance and expressivity.…”
Section: Parkinson's Disease Geneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, family studies have revealed monogenic forms of PD in which variation at a single gene locus can be attributed to disease causality [8]. For example, PD-causing autosomal dominant mutations have been identified in the LRRK2, SNCA, and VPS35 genes, and autosomal recessive mutations have been identified in the PARK7 (Dj-1), PRKN (Parkin), and PINK1 genes [7][8][9][10][11]. While the development of single gene disorders is primarily determined by genetics, known and unknown factors can modify disease penetrance and expressivity.…”
Section: Parkinson's Disease Geneticsmentioning
confidence: 99%
“…In the context of PD, highly penetrant causal variants, such as triplications 2 H.M. Bailey and M.R. Cookson / LRRK2 in CNS cells of the SNCA gene, are rare, whereas variants with variable penetrance, such as those found at the LRRK2 or GBA loci, occur more frequently in the population [7,10]. Adding to this complexity, PD-linked gene variants can also display variable expressivity, in which patients with the same pathogenic genotype may exhibit varying clinicopathological phenotypes [13][14][15][16].…”
Section: Parkinson's Disease Geneticsmentioning
confidence: 99%
See 1 more Smart Citation